The influence of simulation time-resolution on the matching between on-site micro-wind generation and building electric demand. Issue 5 (2nd September 2016) - Cao, Sunliang; Sirén, Kai
Abstract : This paper is to investigate the unique impact of simulation time-resolutions on energy matching between on-site micro-wind turbine and household electric demand. The focused indices are on-site electrical energy fraction (OEFe), on-site electrical energy matching (OEMe), and their errors (eOEF and eOEM ). The methodology consists of parametric analyses with respect to time-resolution levels, averaging methods, demand profiles, turbine capacities, and wind conditions. Two averaging methods are used: 'Speed Averaging' and 'Power Averaging'. With a coarser resolution, two averaging effects have been found. One is an overestimation effect by both the averaging methods, which are more likely to be encountered especially when a high-resolution generation curve frequently crosses intermittent long spikes of a demand curve. The other effect is an underestimation effect on OEFe simultaneously occurring with the Speed Averaging Method under the conditions of (1) a low wind speed and (2) a high unstable wind speed and a low turbine capacity.